Determinants of farmers’ access to microcredit from cooperative societies in Ondo state, Nigeria - Kolapo, A; Ogunleye, AS; Kehinde, AD; Adebanke, AA (International Journal of Agricultural Research, Innovation and Technology, 2022)
The study examined the determinants of farmers’ access to microcredit from cooperative societies in Ondo state. A multistage sampling technique was used to obtain data from 100 respondents. Primary data was collected for the purpose of the study. We used descriptive statistics and logit regression model to analyses the data collected. Result showed that the farmers were mostly male farmers (64%) while majority of the farmers had a mean age of 44.10 ± 14.70. It was also revealed that consumer cooperative society, producer cooperative society, marketing cooperative society, cooperative farming society and credit and thrift cooperative society were the major forms of cooperative used by the farmers. The result also shows that age, marital status, farm size, farming experience, credit from another source and number of years in the cooperative significantly influenced farmers’ access to microcredit from cooperative society. Int. J. Agril. Res. Innov. Tech. 11(2): 103-107, Dec 2021